2016
DOI: 10.1007/s10495-016-1222-9
|View full text |Cite
|
Sign up to set email alerts
|

Profilin potentiates chemotherapeutic agents mediated cell death via suppression of NF-κB and upregulation of p53

Abstract: The molecular mechanism by which Profilin acts as a tumor suppressor is still unclear. Several chemotherapeutic agents, used till date either have unfavorable side effects or acquired resistance in tumor cells. Our findings show that Profilin enhances cell death mediated by several chemotherapeutic-agents. The activation of NF-κB and its dependent genes, mediated by paclitaxel and vinblastine, was completely inhibited in Profilin overexpressing cells. This inhibition was due to the Profilin mediated attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Profilin 1 plays a double role in the regulation of osteoclast differentiation. On one hand, it directly suppresses NF‐κB activity, a key molecule for osteoclast formation and survival . In addition, PFN1 directly interacts with and prevents the degradation of the phosphatase PTEN, known to negatively regulate osteoclast differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…Profilin 1 plays a double role in the regulation of osteoclast differentiation. On one hand, it directly suppresses NF‐κB activity, a key molecule for osteoclast formation and survival . In addition, PFN1 directly interacts with and prevents the degradation of the phosphatase PTEN, known to negatively regulate osteoclast differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting the NF-κB pathway enhances the antitumor effect of cabazitaxel by downregulating Bcl-2 in pancreatic cancer ZEQUN LI [1][2][3][4] , ZEFENG XUAN [1][2][3][4] , JIAN CHEN [1][2][3][4] , WENFENG SONG [1][2][3][4] , SHIYU ZHANG [1][2][3][4] , CHENG JIN [1][2][3][4] , MENGQIAO ZHOU [1][2][3][4] , SHUSEN ZHENG [1][2][3][4] and PENGHONG SONG [1][2][3][4] gene (14,15). Furthermore, the downregulation or inhibition of NF-κB activation is an effective treatment option for certain types of cancer, including colorectal cancer, glioblastoma, breast cancer and lung cancer (16,17). It has been reported that NF-κB p65 directly bound to NME5 serves a central role in PC chemoresistance by inhibiting gemcitabine-induced apoptosis and G1 phase arrest (18).…”
Section: Introductionmentioning
confidence: 99%
“…Low expressions of CAP‐G, HSP27 and L‐plastin were reported in vincristine‐resistant ALL (Verrills et al , , ) and a low expression of HSP27 was observed in doxorubicin‐resistant uterine cancer cells (May et al , ). Moreover, the high expression of myosin‐9 sensitized acute myeloid leukaemia cells to apoptosis by the alkaloid homoharringtonine (Zhang et al , ) and Profilin‐1 potentiated several chemotherapeutic agents (including doxorubicin) to mediate cell death via the suppression of NF‐κB and upregulation of p53 (Zaidi et al , ). However, some actin‐related proteins in our study were reported to correlate with poor prognosis in other cancers, including S100‐A11, cofilin‐1, fibrillin‐1 and Rap‐1b.…”
Section: Discussionmentioning
confidence: 99%